2022
DOI: 10.1186/s13071-022-05153-6
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide molecular surveillance of three Plasmodium species harboured by symptomatic malaria patients living in Ghana

Abstract: Background Clinical presentations of malaria in Ghana are primarily caused by infections containing microscopic densities of Plasmodium falciparum, with a minor contribution from Plasmodium malariae and Plasmodium ovale. However, infections containing submicroscopic parasite densities can result in clinical disease. In this study, we used PCR to determine the prevalence of three human malaria parasite species harboured by suspected malaria patients attending healthcare facilities across the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…The high prevalence of asymptomatic malaria recorded in the study confirms previous reports that malaria is hyperendemic in Osun State [23]. It was previously observed that the majority of individuals infected with malaria parasites living in endemic regions do not show symptoms of this disease [24]. The high prevalence of malaria parasites could be a reflection of the poor socioeconomic condition of the study area, which promotes the transmission of malaria, especially during the rainy season.…”
Section: Discussionsupporting
confidence: 86%
“…The high prevalence of asymptomatic malaria recorded in the study confirms previous reports that malaria is hyperendemic in Osun State [23]. It was previously observed that the majority of individuals infected with malaria parasites living in endemic regions do not show symptoms of this disease [24]. The high prevalence of malaria parasites could be a reflection of the poor socioeconomic condition of the study area, which promotes the transmission of malaria, especially during the rainy season.…”
Section: Discussionsupporting
confidence: 86%
“…In Ghana, approximately 75% of malaria cases are caused by P. falciparum , and some are caused by P. malariae and P. ovale . 9 For our patient, PCR was positive only for P. falciparum during both admissions. Clear distinction between isolated gametocytemia and treatment failure is necessary for effective treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Another finding worth nothing was that, all the other non-falciparum species identified, co-infected with the falciparum species. However, this is not new in Ghana, since a previous study has recorded almost the same prevalence (0.7%) of Pf/Po in a nationwide study that analysed 5260 samples [ 28 ]. The other mixed-infection that was found in this study was Pf/Pv/Pm .…”
Section: Discussionmentioning
confidence: 94%